(3GdLGeY deG aj GdeUfaGJ GdLhGeY ef CSeGA GdUMGHI GdCYdGe Chdi GdaVGFd hGdCMdGes - (3YjSi Hf SdjeGf Hf YHO Gddg GdQYjfj, CHh ehSi,J (B632 (3g` s
(3ChdgG (B:s
(3HOC GdehLhO efg HJQLeI eMeO Hf KGHJ Hf bjS Hf TeGS GdCfUGQi s
(3BNQgG (B:s
(3jfJgi HJQLeI Ce jMji Hbhdg Ce jMji GeQGAI CSjO Hf NVjQ BNQ cJGH GdLGeY deG ai GdeUfaGJ GdLhGeY ef GSeGA GdUMGHI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B103s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs